Manejo em pomares de figueira com duas cultivares, diferente número de ramos e densidade de plantio avaliando produtividade e qualidade dos frutos - Ecker, Scheila Lucia (2017)
The fig tree (Ficus carica L.) is one of the oldest cultivated species, characterized by its great capacity for adaptation to edaphoclimate, although it is considered a temperate climate species. In Brazil, the production of fig coincides with the world off season, allowing better profits to the producer and the country. The objective of this work was to evaluate different cultivars, number of branches conducted in the plants and density of fig tree orchards for productive improvement and fruit quality. Two experiments were carried out in a fig tree orchard near the experimental area of the Fronteira Sul Federal University - Chapecó / SC campus. Experiment 1: a completely randomized experimental design with three replicates, each replicate composed of four plants, in a 2x3 factorial scheme, two cultivars (Roxo de Valinhos and Pingo de Mel) and three different numbers of branches (16, 24 and 32 branches.plant-1). Experiment 2: a randomized complete block design was used, with three replicates, each replicate being composed of five plants, which were submitted to three different planting spacings; 1) 5 x 0.5 m; 2) 5 x 1.0 m; And 3) 5 x 1.5 m. As for the productivity for the experiment 1, it was observed that the cultivar Roxo de Valinhos was superior to Pingo de Mel, especially when conducted with a greater number of branches, for the accumulated productivity. For experiment 2, the yield for both mature fruits and for green fruits and accumulated productivity was higher for plants conducted in smaller densities, indicating that less densified plants have a higher light absorption, consequently greater photosynthesis, directly interfering with productivity.